OsHsfA2c and OsHsfB4b are involved in the transcriptional regulation of cytoplasmic OsClpB (Hsp100) gene in rice (Oryza sativa L.) - Amanjot Singh; Dheeraj Mittal; Dhruv Lavania; Manu Agarwal; Ratnesh Chandra Mishra; Anil Grover (2011)
ClpB-cytoplasmic (ClpB-cyt)/Hsp100 is an important chaperone protein in rice. Cellular expression of OsClpB-cyt transcript is governed by heat stress, metal stress, and developmental cues. Transgenic rice plants produced with 2 kb OsClpB-cyt promoter driving Gus reporter gene showed heat- and metal-regulated Gus expression in vegetative tissues and constitutive Gus expression in calli, flowering tissues, and embryonal half of seeds. Rice seedlings regenerated with OsClpB-cyt promoter fragment with deletion of its canonical heat shock element sequence (HSE(-273 to -280)) showed not only heat shock inducibility of Gus transcript/protein but also constitutive expression of Gus in vegetative tissues. It thus emerges that the only classical HSE present in OsClpB-cyt promoter is involved in repressing expression of OsClpB-cyt transcript under unstressed control conditions. Yeast one-hybrid assays suggested that OsHsfA2c specifically interacts with OsClpB-cyt promoter. OsHsfA2c also showed binding with OsClpB-cyt and OsHsfB4b showed binding with OsClpB-cyt; notably, interaction of OsHsfB4b was seen for all three OsClpB/Hsp100 protein isoforms (i.e., ClpB-cytoplasmic, ClpB-mitochondrial, and ClpB-chloroplastic). Furthermore, OsHsfB4b showed interaction with OsHsfA2c. This study suggests that OsHsfA2c may play a role as transcriptional activator and that OsHsfB4b is an important part of this heat shock responsive circuitry.